Audio visual isolated Hindi digits recognition using HMM. (2015) - Biswas, Astik; Sahu, P.K.; Chandra, Mahesh
Automatic speech recognition (ASR) system performs well under restricted conditions but the performance degrades under noisy environment. Audio-visual features play an important role in ASR systems in presence of noise. In this paper, Hindi isolated digits recognition system is designed using audio visual features. The visual features of the lip region integrated with audio features to get better recognition performance under noisy environments. Colour intensity and pseudo hue methods have been used for lip localisation approach with hidden Markov model (HMM) as a classifier. Recognition performance using HMM is better than LDA recogniser. For image compression, principal component analysis technique has been utilised.